Innovation and Six Sigma foundation from the perspective of the absorptive capacity theory - Yusr, Maha Mohammed; Othman, Abdul Rahim; Mohd Mokhtar, Sany Sanuri (2011)
There are many strategies and initiatives that have been applied in different organizations, and Six Sigma is one of these strategies. By applying Six Sigma, organizations aim to achieve a high rate of performance. The effect of Six Sigma on the business performance has drawn the attention of many scholars. Since Motorola’s release of Six Sigma as a quality strategy, researchers have studied the relationship between Six Sigma and many aspects of business performance whether financial or non-financial aspects.But there are some aspects of the organization that still need to be investigated and elaborated.The relationship between Six Sigma and innovation is one of the organization aspects that needs to be deeply investigated.(Parast, 2010).Although reviewing the literature related to Six Sigma hints that Six Sigma helps organizations to be innovative via one of the approaches that belongs Six Sigma which is DFSS, there is no an explicit study that explains the effect of Six Sigma as a strategy on the innovative abilities of the organization.Thus, the present paper aims to introduce a theoretical study that investigates and explains this relationship between Six Sigma and innovation from the Absorptive Capacity Theory perspective.